SIKU (SISTEM KUARTET UNTUK INGGRIS): REDESIGNING A QUARTET CARD GAME BASED ON PACITAN LOCAL WISDOM TO ENHANCE STUDENTS’ ENGLISH VOCABULARY - Apriyanti, Chusna; Wibowo, Agung; Hadi, Samsul (Universitas Lambung Mangkurat, 2024)
The main objective of this research is to design and develop a quartet card game that integrates Pacitan’s local wisdom to enhance students’ English vocabulary. Mastery of English is crucial in today’s globalised world, yet Indonesian students’ proficiency remains low. Effective and engaging learning materials, like the quartet card game, can help improve English skills. This research uses the Research and Development (R&D) method with the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The analysis stage involved needs assessment and learning context analysis. The design stage created an initial quartet card game based on Pacitan’s local wisdom. In the development stage, a prototype was made and tested. The implementation stage used the game in classroom learning. The evaluation phase assessed the game’s effectiveness by measuring students’ vocabulary enhancement and their responses. Results showed that the SIKU card game effectively enhanced students’ English vocabulary and increased their motivation and interest in learning English. The positive response from students indicates that integrating local wisdom into learning media makes the learning process more engaging and meaningful. This research contributes to education by developing innovative, local wisdom-based learning media, enriching learning materials, and strengthening students’ cultural identity.